ANALISIS KEMAMPUAN KOMUNIKASI INTERPERSONAL GURU DAN PENGARUHNYA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Tutut Rahayu Astuti; Elvira Destiansari; Gusmelia Testiana (Bioilmi: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the teacher's interpersonal communication and its effect on the learning motivation of seventh grade students in science subjects VII at MTs 'Aisyiyah 1 Palembang. The method used in this research is descriptive quantitative with a sample of all students with a total of 85 students. The teacher's interpersonal communication questionnaire and the students' learning motivation questionnaire were used as a data collection tool and then analyzed. The average percentage of teacher interpersonal communication is 80.91% and the percentage of students' learning motivation is 83.60% which is categorized as very high. Interpersonal communication of teachers has an influence on students' learning motivation. Good interpersonal communication by the teacher affects the learning motivation of students. Interpersonal communication of teachers is very important and needs to be done to students. If the learning motivation of students is higher, it is expected that in the end the learning achievement of students will also increase.